Comparison of Specifications, Short Term Outcome and Prognosis of Acute Myocardial Infarction in Opium Dependent Patients and Nondependents - Mohammad Alidoosti; Soodabeh Darvish; Shahin Akhondzadeh; Saeed Sadeghian; Gholamreza Davoodi; Alireza Amirzadegan (Journal of Tehran University Heart Center, 2006)
Background: The effects of opium dependence on prognosis and short term outcome of patients with acute myocardial infarction (AMI) are not clear yet. Methods: From March 2004 to August 2004 all male patients admitted with diagnosis of AMI were enrolled. Patients who fulfilled DSM- IV-TR criteria were chosen as opium dependent patients (ODP). Demographic data, risk factors, peak enzyme levels, location of MI, mortality and ejection fraction were collected and analyzed. We studied the mortality, readmission, functional class, performed revascularizations and coronary angiogram results in a short term follow-up (184 ± 37 days). Results: A total number of 160 patients were enrolled, of which 45 (28.1%) were opium dependent. In 137 patients 6 months follow up was completed. Duration of admission was higher in O.D.P (11.3 days versus 8.7, P= 0.03) There was no significant difference in age, EF, location of MI, peak enzymes levels, angiographic findings, risk factors (except for cigarette smoking and triglyceride level), in-hospital mortality, need for readmission, 6 months mortality, functional class, and the need for revascularization. Conclusion: In an unselected cohort of patients admitted with AMI, there was no significant difference in specifications, short term outcome and prognosis of AMI between ODP and nondependents except for duration of hospitalization.